Identifying the performance drivers of wastewater treatment plants through conditional order-m efficiency analysis. (October 2016) - Guerrini, Andrea; Romano, Giulia; Mancuso, Fabrizio; Carosi, Laura
Abstract: In European countries, wastewater treatment service is often provided by utilities, which have to comply with environmental laws and, at the same time, should control costs in order to restrain tariff growth and earn profits. By applying a conditional order-m efficiency method, this study provides some insights to the operational variables affecting the efficiency of 137 plants owned by a water utility operating in Tuscany, Italy. These performance drivers are categorized as: 1) wastewater features, 2) plant technology, 3) other plant features, 4) output quality, and 5) sludge disposal method. Starting from some controversial results from prior literature, this paper provides some useful insights on the best policies that could be adopted by a utility to catch cost savings. Highlights: This paper might help plant managers to find the correct target for each measure, in order to improve the treatment process. Before choosing to invest in a new technology benefits and costs arising from this choice must be accurately evaluated. When building a new plant, its size must be well matched to the extension of the area served, in terms of inhabitants. Wastewater features, plant features and technology, output quality, and sludge disposal method affects cost efficiency.